Analysis of NCDEX Spices Spot and Futures Trading - Arpit Joshi; Manish K. L.; M. S. Ganapathy; Channaviragouda (Archives of Current Research International, 2024)
This research paper evaluates the efficacy of spot and futures trading in spices on NCDEX by analysing the relationship between spot prices and futures trading. The study uses daily spot and near-month futures price data from financial year 2015-16 to financial year 2021-22, encompassing 1,777 observations. The ADF test confirmed that both spot and futures prices are stationary at the first difference, while Johansen’s cointegration test revealed a significant long-term relationship between these prices for Jeera, Turmeric, and Coriander, with trace values of 67.24, 39.42, and 36.21, respectively. Granger causality tests showed a unidirectional relationship in Jeera and a bidirectional relationship in Turmeric and Coriander, indicating the futures market’s dominant role in price discovery for Jeera and its shared importance with the spot market for Turmeric and Coriander. These findings suggest that the futures market on NCDEX plays a vital role in price discovery and risk management, making it an essential tool for stakeholders in the Indian agricultural commodity market.